Individual Differences: An Asset for Learning and Teaching - Pandey, Shiv Ram (Madhyabindu Journal, 2022)
The paper presents the individual differences of the learners in the learning and teaching process. The purpose of this paper is to explore how individual learners learn the language with differences. It is a theoretical article which explores learning styles and strategies the second language learners use while learning the language. The available relevant literature has been reviewed, analyzed and linked with life for learning. The paper concludes that student diversity is a natural phenomenon in student learning. Instead of taking it as problematic, it can be viewed as a valuable resource for promoting effective learning and teaching. It is expected that the relevant stakeholders should respect diversity to bring multiple knowledge, experiences and creativity in teaching and learning process.